INITIAL VALIDATION OF THE CAREER COUNSELLING SELF-EFFICACY SCALE IN MALAYSIAN PUBLIC UNIVERSITIES - Amat, Aden E; Mahmud, S.; Ghazali N.M, M.I.; A., Annuar (International Journal of Psychosocial Rehabilitation, 2020)
The purpose of the research is to translate The Career Counselling Self-Efficacy Scale (CCSS) from English to Malay version. There were no critical issues raised by the experts during the process of validity. The back-translation method was utilized in the translation process. The Malay version of CCSS has been pre-tested to obtain feedback for improvement. Results of the corrected item-total correlation for the sub-scale is above .25, while, results for the pilot tests conducted on the undergraduate and postgraduate students at two Public Universities in Malaysia, have reported that the validity value was (α=.85). The Cronbach's Alpha Value of the 25 item is .98 indicating that the items were designed accordingly to the Malaysian cultural context. This study has illustrated that the counselor's training could increase the level of counselor's competence and provided.